Community Participation in Sustainable Cultural Heritage Tourism in The Braga Tourism Village - Baswarani, Delfta Tunjung; Novianto, Untung (Centre For Tourism Planning and Development, 2025)
This study aims to examine community participation in the development of sustainable cultural heritage tourism in Braga Tourism Village, Bandung City. Initiated by the Bandung City Office of Culture and Tourism (DISBUDPAR) through a top-down approach as part of a tourism village activation program, the implementation of this initiative has raised concerns regarding the limited involvement of local residents. A descriptive qualitative approach was employed, with data collected through document analysis, field observations, and in-depth interviews with key stakeholders including street vendors, tourism awareness groups, village officials, and representatives of the local tourism office. Data were analyzed using Miles and Huberman’s interactive model through data reduction, display, and conclusion drawing. The findings reveal that while the initial planning was government-driven, local communities have gradually taken the lead in sustaining tourism activities by initiating creative and community-based programs. Public facilities and government-provided training have supported tourism development, yet the optimization of these resources remains limited due to insufficient community capacity. Moreover, the preservation of cultural heritage particularly Braga’s historic buildings and urban identity has been maintained through a combination of formal regulations and civic engagement. The study concludes that the success of sustainable tourism in urban heritage settings such as Braga depends on effective collaboration between government and communities, with local residents playing a central role in preserving cultural values while deriving socio-economic benefits.